"Matter of glorious trial" : spiritual and material substance in Paradise lost - Sugimura, N. K. (Yale University Press, 2009)
This groundbreaking book, the first to examine Milton's thinking about matter and substance throughout his entire poetic career, seeks to alter the prevailing critical view that Milton was a monist-materialist-one who believes that all things are composed of material and all phenomena (including consciousness) are the result of material interactions. Based on her close study of the philosophical movements of Milton's mind, Sugimura discovers the "fluid intermediaries" in his poetry that are neither strictly material nor immaterial. In doing so, Sugimura uses Paradise Lost as a fascinating window into the intersection of literature and philosophy, and of literary studies and intellectual history. Sugimura finds that Milton displays a tense and ambiguous relationship with the idealistic dualism of Plato and the materialism of Aristotle and she argues for a more nuanced interpretation of Milton's metaphysics.